ANALISIS RANGKAP JABATAN PADA PT POS INDONESIA REGIONAL V SURABAYA - Intan, Tabina; Amalina Rizqi, Maulidyah (BJRM (Bongaya Journal For Research in Management), 2024)
Despite being a state-owned enterprise with strategic importance in logistics and communication, the company faces challenges in its human resource management, particularly in filling critical vacancies. This issue has led to the practice of dual positions, which compromises both employee productivity and operational efficiency. This study aims to analyze the factors causing dual positions and their impact on employees at PT Pos Indonesia Regional V Surabaya. The research employed a descriptive qualitative method through unstructured interviews and observations within the Financial Business Partner and Asset division. Data analysis utilized the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results revealed that dual positions occurred due to vacant roles caused by employee transfers without replacements, leading to an increased workload that negatively impacted productivity and heightened work pressure. Although work quality was considered fairly good, task completion deadlines were often disrupted. It is recommended that the company promptly recruit or transfer employees to fill the vacancies to reduce workload and improve operational efficiency.